2009
DOI: 10.1097/rli.0b013e31818c3d6b
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Computed Tomography Angiography With Automated Bone Subtraction

Abstract: Automatic subtraction provides diagnostic image quality for 3D visualization of intracranial vessels, free from over projecting bone in a fully automatic way. Aneurysms can be evaluated from all angles, and ICA stenoses at the skull base were easily visualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…More recently, fully automated bone subtraction CTA was developed by Lell el al. [25] who found that bone subtraction CTA may speed up vascular assessment and improve diagnosis. In another study of 100 patients, Morhard et al demonstrated that bone subtraction CTA can improve the delineation of vasculature closely adjacent to bony structures [26].…”
Section: Discussionmentioning
confidence: 97%
“…More recently, fully automated bone subtraction CTA was developed by Lell el al. [25] who found that bone subtraction CTA may speed up vascular assessment and improve diagnosis. In another study of 100 patients, Morhard et al demonstrated that bone subtraction CTA can improve the delineation of vasculature closely adjacent to bony structures [26].…”
Section: Discussionmentioning
confidence: 97%
“…17,21 Bone-subtraction CTA 22,23 has been developed to overcome this problem. A feasibility study 22 and a study with 100 patients 24 showed that BSCTA can improve the detection of vascular pathology closely adjacent to bony structures. These studies, however, did not use DSA as the reference standard to determine the diagnostic accuracy of BSCTA under clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques can be based on subtraction of a nonenhanced scan from the CTA 12,13 or on masking highly attenuating bony structures from the data. 14,15 Although multiple studies have shown that bone removal in CTA improves vascular analysis, 13,16,17 it is not routinely used in clinical practice because either the required techniques are not available (eg, dual-energy) or the removal is too time-consuming when user interaction is required. Furthermore, some methods remove part of the vessel wall, 12 which decreases diagnostic confidence.…”
Section: Discussionmentioning
confidence: 99%